Private and public incentive to reduce seasonality: A theoretical model - Roberto Cellini; Giuseppe Rizzo (Kiel Institute for the World Economy (IfW), 2012)
This paper presents a theoretical model to investigate the incentive of private producer and policymaker to reduce seasonality in a given market, where consumers derive different utilities from the consumption of the good in different seasons. The (seasonal) product differentiation is modelled along the lines of the contributions of Gabszewicz and Thisse (Price Competition, Quality and Income Disparities, 1979) and Shaked and Sutton (Relaxing Price Competition through Product Differentiation, 1982). The authors take into consideration that investments are possible to reduce the degree of seasonality. They show that, for a wide set of parameter configuration, the policy maker finds it optimal to make more effort to reduce seasonality as compared to private producers. The theoretical conclusion is consistent with empirical and anecdotical evidence, especially in the field of tourism markets.
Keywords: D29; L12; L83; 330; seasonality; tourism; public spending